Impact of Lobar Resection Site on Postoperative Pulmonary Function in Non-Malignant Lung Disease - Karmakar, Rajeebshankar; Akond, Atik Ahmed; Noor, Masnoon Ahmed; Supti, Sutopa Halder; Jahan, Israt; Biswas, Sushit Kumar (Faridpur Medical College Journal, 2026)
Background: Pulmonary lobectomy often leads to significant postoperative declines in lung function, influenced by lobar location and anatomical changes. Since most research focuses on malignancies, this study aims to bridge the gap by exploring how lobar site affects functional outcomes in non-malignant cases. Materials & Methods: This cross-sectional analytical study, conducted over 18 months at NIDCH, included 54 patients who underwent lobectomy for non-tubercular diseases and met specific inclusion criteria. Eligible participants were adults capable of performing spirometry and diagnosed with various benign pulmonary conditions, while those with severe systemic illnesses, pulmonary malignancy, or active tuberculosis were excluded. Two months after surgery, face-to-face interviews and pulmonary function tests were performed to assess postoperative outcomes. Results: The demographic and clinical characteristics across lobectomy groups were largely comparable, with no significant differences in age, sex, BMI, smoking history, or comorbidities, ensuring a balanced baseline. Bronchiectasis was the most common diagnosis, especially in bilobectomy and LUL cases, while aspergilloma and other conditions appeared less frequently and varied by lobar site. Preoperative pulmonary function tests showed consistent values across all groups, affirming uniform baseline respiratory status. Postoperatively, there was a universal decline in FEV1, FVC, and FEV1/FVC across all lobectomy types, with the most marked reductions seen in bilobectomy and lower lobe resections, highlighting the significant impact of lobar location on pulmonary function. Conclusions: This study highlights the critical role of lobar location in determining postoperative pulmonary function after lobectomy for non-malignant lung diseases. Despite limitations, the findings emphasize the need for site-specific surgical planning. Faridpur Med. Coll. J. 2026;21(1):45-50